Radical‐Based C−C Bond‐Forming Processes Enabled by the Photoexcitation of 4‐Alkyl‐1, 4‐dihydropyridines. Issue 47 (24th October 2017) - Buzzetti, Luca; Prieto, Alexis; Roy, Sudipta Raha; Melchiorre, Paolo
Abstract: We report herein that 4‐alkyl‐1, 4‐dihydropyridines (alkyl‐DHPs) can directly reach an electronically excited state upon light absorption and trigger the generation of C(sp 3 )‐centered radicals without the need for an external photocatalyst. Selective excitation with a violet‐light‐emitting diode turns alkyl‐DHPs into strong reducing agents that can activate reagents through single‐electron transfer manifolds while undergoing homolytic cleavage to generate radicals. We used this photochemical dual‐reactivity profile to trigger radical‐based carbon–carbon bond‐forming processes, including nickel‐catalyzed cross‐coupling reactions. Abstract : Powered by light : 4‐alkyl‐1, 4‐dihydropyridines1 are primarily understood as hydride sources in their ground state. Excitation with a violet‐light‐emitting diode transforms them into strong reducing agents that can activate reagents through single‐electron transfer while undergoing homolytic cleavage to generate alkyl radicals. This process was used to trigger radical‐based C−C bond‐forming processes, including nickel‐catalyzed cross‐coupling reactions.